PERBANDINGAN RASIO KELAMIN, MORTALITAS DAN PERTUMBUHAN IKAN NOMEI (Harpadon nehereus) YANG BERASAL DARI HASIL PENANGKAPAN NELAYAN JUATA KOTA TARAKAN - Indra Perdana; Gazali Salim; Encik Weliyadi (Jurnal Harpodon Borneo, 2016)
The aim of research was to determine the sex ratio test; fish mortality and growth of fish nomei in waters Juata Tarakan City. Method location research is purposive sampling with consideration that the research sites is the main area of fishing nomei in the waters Juata Tarakan City. The variable in this study is the variable sex ratio, mortality, growth allometri, condition index, absolute growth, age structure. Sample collection technique using field surveys. The sampling method by using the technique of "purposive sampling". Primary data obtained from data on length and weight of the fish that fishermen catch nomei performed 5 times a cycle arrest for 3 months for a total of as many as 50 fish of various sizes. Fish samples measured length (cm) and weight (grams). Sampling as many as 50 fish nomei using purposive sampling method is expected to represent the population of fish nomei in the waters Juata Tarakan City.The result showed that the sex ratio is 43.2% male and 56.8% female. The maximum length of male and female fish nomei is 32.2 cm average growth rate of 0,019 cm / day and by 34 cm with a growth rate of 0,017 cm / day. Nomei male and female fish that are allometri positive and negative. The mortality rate of male and female fish that is equal to3.88% per three months and 6.97% per three months. Keywords : Harpadon nehereus; mortality; kelammin ratio; growth; Tarakan